Diálogos sobre a história social da infância e o reconhecimento da criança como sujeito de direitos pelo Estatuto da Criança e do Adolescente (1990) - Martins, Ludmila Gonçalves (2012)
History is a science that concentrates its attention on the study of long-term phenomena, and such specificity leads the labor of this study to place into historical perspective definitions and concepts that, albeit not being significantly set back in time, manifest permanence and continuity. Thus, the present work purports to discourse about the speeches of childhood in contemporaneity, especially during the Republican period in Brazil, having as a goal to analyze the political and judicial discourse that have been construed around the category childhood . As a specific goal, this research brings a discussion about the institutionalization of the child in the Brazilian republican political project, emphasizing the legal frameworks of the Juvenile Code (1927 e 1979) and of the Child and Adolescent Statute. In this sense, concerning the shift in paradigm from the conception of minors to the statutory doctrine, one can say that children and adolescents started being recognized as subjects endowed with rights and not any longer as objects of legal measures. In this manner, we intend to understand how social control upon the child happens and contributes to the creation of the State s parental responsibility discourse, as well as to understand how the process of institutionalization of the child as a subject endowed with rights took place.